BIMBINGAN KELUARGA PADA PERILAKU REMAJA YANG ADIKSI GAME ONLINE - Salfia, Wa Ode; Alwi, Alimin; Andi Kamaruddin, Syamsu; Najamuddin (SOSIOLOGI: Jurnal Ilmiah Kajian Ilmu Sosial dan Budaya, 2024)
Online games tend to have a negative impact, but not on adolescents in Matara Village, Central Buton Regency. This research aims to complement the shortcomings of previous studies by highlighting the role of family guidance in overcoming online game addiction in adolescents. This research is a qualitative research with case study type. The informants in this study are parents and adolescents who are addicted to online games. Data collection techniques start from participatory observation, in-depth interviews and documentation. This study reveals that family guidance towards adolescents is by controlling adolescents' activity time, providing independent thinking space for children, and inviting adolescents to save money. The factors of online game addiction are freedom of feelings, friendship environment, and free time. This study shows that family guidance is effective in overcoming the negative impact of online game addiction and turning it into a sustainable positive impact.  The results of this study suggest that online games can help provide a positive impact on children if they are well controlled in their use.